Tools for Transparency in Central Government Spending - Rahal, Charles (International Journal of Population Data Science, 2019)
We first introduce centgovspend, an open source software library which provides functionality to automatically scrape and parse central government spending within the United Kingdom at the micro and meso levels. The library then optionally reconciles suppliers and subsequently analyzes payments made to private entities. We briefly discuss the policy environment surrounding the library before explaining the modular structure, implementation and execution which results in scraping over 4.9m payments worth over £3.5tn in value. We then provide two prototype applications in the fields of public administration and sociology; one of which analyzes government procurement across Standard Industry Classifier (SIC) and one which analyzes the social stratification of company officers and persons of significant control who supply the government. The project acts as a prototype in an international context, aiming to highlight an unrealised possibility of 'Big, Open Data' for public policy making and government efficiency.